2020
DOI: 10.1111/jpn.13332
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Escherichia coli phytase expressed in Lactococcus lactis on nutrient retention, bone traits and intestinal morphology in broiler chickens

Abstract: The availability of plant phosphorus in the gut chicken can be improved by increasing phosphorus retention using phytase enzyme or a probiotic with phytase activity as an alternative. In this study, the efficacy of a recombinant probiotic, Lactococcus lactis (L. lactis), with a potential of phytase production was evaluated in broiler chickens. To this aim, 360 one-day-old male broiler Cobb 500 were divided into six treatments with six replicates and reared to 42 days of age. The experimental treatments include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…The intestinal morphology had a decisive influence on the intestinal epithelial area, and the raised villus greatly increased the surface area of intestinal epithelium that increased nutrient absorption [ 40 ]. E. faecium PNC01 reduced FCR by increasing the villus height of the intestinal epithelium, which was consistent with the previous results that LAB increased the villus surface area [ 13 ]. The intestinal crypts mainly secreted digestive enzymes, and the crypts became shallower in depth after differentiation and maturation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The intestinal morphology had a decisive influence on the intestinal epithelial area, and the raised villus greatly increased the surface area of intestinal epithelium that increased nutrient absorption [ 40 ]. E. faecium PNC01 reduced FCR by increasing the villus height of the intestinal epithelium, which was consistent with the previous results that LAB increased the villus surface area [ 13 ]. The intestinal crypts mainly secreted digestive enzymes, and the crypts became shallower in depth after differentiation and maturation.…”
Section: Discussionsupporting
confidence: 92%
“…Study has showed that Lactobacillus spp. improved the crude protein retention and meat quality in animals [ 13 , 14 ]. Short-chain fatty acids such as butyrate produced by intestinal microorganisms fermentation in chickens improved the proliferation of intestinal epithelial cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current findings also suggest that, regardless of lower dietary ME and CP–LAA levels, PHY supplementation in the diet has a positive effect on bone mineralization by increasing tibial ash and P content. This enhancement in tibia mineralization reported in broilers given a diet supplemented with PHY is comparable with that found in previously published research on broilers (Akter et al., 2016 ; Jing et al., 2021 ; Mohammadi Ziarat et al., 2020 ). In the present work, PHY was employed to dephosphorylate myo‐inositol hexaphosphate, which likely enhanced bone mineralization by improving the bioavailability of ash, P and Ca.…”
Section: Discussionsupporting
confidence: 91%
“…The results of these investigations have consistently shown that PHY supplementation enhances dietary phosphorous availability across all studies and species studied. In addition, multiple studies have shown that PHY increases the availability of other minerals (Akter et al., 2016 ; Mohammadi Ziarat et al., 2020 ) and amino acids (Jing et al., 2021 ; Jlali et al., 2020 ), which in turn enhances growth rate and bone mineralization. A recent study conducted on broiler chickens (Moss et al., 2020 ) has shown that PHY supplementation increased starch digestibility and energy utilization of maize‐ and wheat‐based diets, which was associated with an increase in NSP digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects depend on the degree of AP reduction in the diet. For example, Ziarat, Kermanshahi, Mogaddam and Heravi (2020) at the initial phase in broilers fed P-deficient diets, and related the lack of response to the The WG of birds in treatments NC1 and NC2 was lower in the period from 1 to 21 days, compared to birds in treatments PC, NC1 + Phy, and NC2 + Phy + E (p < 0.05). The negative effect of AP reduction is not only observed in the birds' food intake; AP deficiency can lead to anorexia and, therefore, to less weight gain (Montanhini, Ceccantini, & Fernandes, 2012;Rahimi, Modirsanei, & Mansoori, 2020).…”
Section: Resultsmentioning
confidence: 99%